Development of low-cost iron mixed porous pellet adsorbent by mixture design approach and its application for arsenate and arsenite adsorption from water - Borano Te; Boonchai Wichitsathian; Chatpet Yossapol; Watcharapol Wonglertarak (Adsorption Science & Technology)
In this study, natural clay, iron oxide, and iron powder were combined to develop low-cost iron mixed porous pellet adsorbent for arsenate and arsenite removal from aqueous solution in batch experiments. The augmented simplex centroid mixture design was applied to obtain the optimum proportion of each constituent. Higher correlation coefficient of the models (R 2  > 0.95), good distribution of residuals, and lower values of p value (<0.05) indicated that the method is suitable for determining the optimum mixture proportion. Extensive decrease of both arsenate and arsenite adsorption occurred in the alkaline condition (pH > 9). Kinetic and isotherm experimental data of both arsenate and arsenite were well described by the pseudo-second order and Sips models, respectively. The maximum adsorption capacity of arsenate and arsenite derived from Sips model were 13.33 and 19.06 mg/g, respectively. The separation and heterogeneity factors showed that both arsenate and arsenite were favorably adsorbed. Among coexisting anions, phosphate significantly showed negative effect on the adsorption of either arsenate or arsenite. The adsorbent could be effectively reused for several times after its regeneration and was considered as non-hazardous material after adsorption.